GOVERNMENT FINAL CONSUMPTION AND HOUSEHOLDS AND HOUSEHOLDS FINAL CONSUMPTION EXPENDITURE IN NIGERIA - USMAN, USMAN A; IDRIS, IDRIS M (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2022)
This study seeks to investigate the effect of Government Final Consumption Expenditure; Financial Deepening on Households, Non-profit institutions serving households (NPISHs) Final consumption expenditure using data on Nigeria spanned 1981 to 2019. This study employed Vector Error Correction Model. The results of the study revealed that the coefficient Government final consumption expenditure has a positive effect on household consumption expenditure in the long run. There is a long run and short run relationship between gross fixed capital formation and household consumption expenditure. The coefficients credit to private secto (cpsgdp) which are financial deepening indicators and gross fixed capital formation posits a negative impact on household final consumption expenditure. The coefficients money supply (lm2gdp) which is another proxy for financial deepening and the coefficient FDI have a positive effect on household final consumption expenditure in the long run. Therefore this study recommends that Gross fixed capital formation stimulates household consumption expenditure, a legal framework to support investment is a panacea to increasing household income, consumption and reduce poverty in Nigeria. Therefore, this should be a key central component for policy. The implication for policy is that government final consumption expenditure stimulates household consumption expenditure positively thus cannot be underscored hence a realistic policy driven towards increasing government final consumption expenditure is strategic to increasing effective and consumption as well